What’s the preferences of medical staff for providing health education service? – A discrete choice experiment in Beijing, China - Qin, Tingting; Gu, Mingyu; Wang, Yao; Yang, Yutong; Guo, Junjun; Li, Xingming; Wang, Yueyong; Gao, Jie; Bai, Yu (Patient education and counseling, 2024)
To quantify medical staff preferences for providing health education service in hospitals. This study took medical staff in the department of internal medicine of hospitals in Beijing, China as the research subjects, and designed a discrete choice experiment (DCE) to investigate the health education service provision preferences of them. Through various methods, 8 attributes and corresponding levels were determined. An online survey was conducted among the medical staff of the sample hospitals from May to June 2023. Participants’ preferences were analyzed using conditional logit and mixed logit models. Finally, 831 respondents completed the questionnaire, among which 600 cases passed the consistency test. All the attributes included in this study had an impact on medical staff’ health education service preferences (P < 0.001). The most important one with the greatest impact on the health education service delivery behavior of the respondents was "department working atmosphere-encouraging health education" (β = 4.062, P < 0.001). In this study, the departmental work atmosphere and performance bonuses emerged as crucial factors influencing the engagement of medical staff in health education work. Hospitals should prioritize measures to improve the health education working atmosphere in departments to increase the enthusiasm of medical staff to provide services. •Staff from different level of hospitals had different importance ranking of factors.•All attributes in this study influence preference for providing health education services.•Department atmosphere was the most significant factor in health education service provision.•Taking targeted measures to enhance the motivation of medical staff in providing services is vital.